Supremely elastic gel polymer electrolyte enables a reliable electrode structure for silicon-based anodes - Qingquan Huang (Nature Portfolio, 2019)
Silicon-based anodes must maintain the electrode structure to fulfil their potential. Here the authors report the use of a supremely elastic gel polymer electrolyte to stabilize such anodes at electrode and particle levels, enabling superior battery performance with a commercial-level capacity.